Perancangan Aplikasi Reservasi Laundry Pada Peach Laundry Jambi Berbasis Web - Yolanda, Imel; Hendri; Mery (Jurnal Informatika Dan Rekayasa Komputer(JAKAKOM), 2024)
Peach Laundry Jambi is one laundry services that are located in Jambi city where data management still use books and counting tools. So that problems occur loss occurs that they should come to data customers and orders data because the notes of destroyed or lost , got mixe up clothing customers caused sameness of name on the notes, calculation error flags or transaction data to name goods and the amount paid and process of the reports that need a relatively long time. Hence this study aims to designing laundry reservation application use PHP programing laungage and DBMS MySQL.This research using waterfall development system and modeling system like use case diagram, activity diagram and class diagram .The result of this research is that this system is hoped to enable in data processing good transaction calculation, a search and the preparation of reports on , so that data processing and dissemination of information become more quickly and correctly